The relationship between nurse managers' leadership style and patients' perception of the quality of the care provided by nurses: Cross sectional survey. (January 2020) - Zaghini, F.; Fiorini, J.; Piredda, M.; Fida, R.; Sili, A.
Abstract: Background: In healthcare systems, human resources play a strategic role that has a significant impact on the whole caring process. When the wellbeing of professionals is low their performance decreases, counterproductive work behaviours may became more likely, and as a result the quality of care is compromised. Studies have shown that leadership style is particularly relevant in relation to the quality of work environments in healthcare organizations. Objective: The main purpose of this study is to test a model that investigates the relationships between nurse managers' leadership style and patients' perception of the quality of the care provided by the nurses, through the mediation of the quality of the working environment (in terms of burnout, interpersonal strain and counterproductive work behaviour). Design: A multi-centre cross-sectional study was conducted. Setting: The study was conducted in five hospitals located two in the north, two in the centre and one in the south of Italy. Participants: Participants were 479 registered nurses (working as staff nurses, while head nurses and nurse managers were excluded) and 829 patients aged 18 years or older, able to read and write Italian and hospitalized for at least 3 days. Severely ill or mentally disabled patients who were not able to fill in the questionnaire were excluded. Methods: The data were collected through two different questionnaires, one for the nurses and one for the patients. A multilevel analysis was conducted to examine the hypothesized model. Results: Results confirmed the hypothesis that, when nurses were satisfied with leadership, they felt less burned-out and strained in interpersonal relationships, they engaged less in misbehaviour, and, in turn, patients were more satisfied with the quality of the care provided by the nurses. Conclusions: The results of this study showed that the characteristics of the organizational context, the leadership, and the behaviours of nurses, influenced patients' perceptions of nurses' care. Therefore, managers of healthcare services should take these results into account seriously in order to improve the quality of care provided to patients.